Applied of actinobacteria consortia-based bioremediation to restore co-contaminated systems - Antezana, Pablo Edmundo (2023)
Global industrialization and natural resources extraction have left cocktails of environmental pollutants. Thus, this work focuses on developing a defined actinobacteria consortium able to restore systems co-contaminated with pollutants occurring in Argentinian environments. In this context, five actinobacteria were tested in solid medium to evaluate antagonistic interactions and tolerance against lindane (LIN), Reactive Black B–V (RBV), phenanthrene (Ph) and Cr(VI). The strains showed absence of antagonism, and most of them tolerated the presence of individual pollutants and their mixtures, except Micromonospora sp. A10. Thus, a quadruple consortium constituted by Streptomyces sp. A5, M7, MC1, and Amycolatopsis tucumanensis DSM 45259T, was tested in liquid systems with individual contaminants. The best microbial growth was observed in the presence of RBV and the lowest on Cr(VI). Removals detected were 83.3%, 65.0% and 52.4% for Ph, RBV and LIN, respectively, with absence of Cr(VI) dissipation. Consequently, the consortium performance was tested against the organic mixture, and a microbial growth similar to the biotic control and a LIN removal increase (61.2%) were observed. Moreover, the four actinobacteria of the consortium survived the mixture bioremediation process. These results demonstrate the potential of the defined actinobacteria consortium as a tool to restore environments co-contaminated with organic pollutants.